(untitled) (International Journal of Food and Nutritional Sciences, 2024)
In today’s world most of the women are suffering from Breast Cancer. The diagnosis of cancer is mostly dependent on histopathological examination of tissue samples. This study suggests using VGG16, which is a deep learning technique, is used to improve the effectiveness of image analysis. VGG16, a convolutional neural network (CNN) is a model used. VGG16 is a fine-tuned to analyse breast tissue, to identify whether it is a Malignant and Benign tissues. Using image samples like BreakHis and various data which we can get from the institutions and hospitals. Through image analysis we find whether the tissue is affected or not. This automated analysis supports pathologists in making quicker and more accurate diagnoses.